Knowledge of infection control practices among intensive care nurses in a tertiary care hospital - Kanwalpreet Sodhi; Anupam Shrivastava; Muktanjali Arya; Manender Kumar (Elsevier, 2013)
Summary: Background: The threat of hospital-acquired infections persists despite advances in the health care system. A lack of knowledge regarding infection control practices among health care workers decreases compliance with these practices. We conducted a study to assess the knowledge of infection control practices among nursing professionals at our hospital. Methods: In total, 100 nurses in the intensive care units at our hospital were given a questionnaire with 40 multiple choice questions, including 10 questions each regarding hand hygiene, standard and transmission-based precautions, care bundles and general infection control practices. The responses were scored as percentages. Results: The overall knowledge and awareness regarding different infection control practices were excellent (>90% positive responses) in 5% of the nursing professionals, good (80-90% positive responses) in 37%, average (70-80% positive responses) in 40% and below average (<70% positive responses) in 18%. Conclusion: The infection control knowledge among the nurses was fairly good; however, there is still a wide scope of improvement with regular educational programs and in-house training. Keywords: Infection control, Hand hygiene, Standard and transmission-based precautions, Care bundles